Toll-like Receptor 4 Gene Polymorphisms in Chinese Population After Allogeneic Hematopoietic Stem Cell Transplantation - Zhao, Yi; Zhang, Yujie; Zhou, Jie; Wang, Lijuan; Shi, Jimin; Tan, Yamin; Luo, Yi; Huang, He; Cai, Zhen (Current Bioinformatics, 2021)
Objectives: Graft-versus-host disease (GVHD) is the most common complication after hematopoietic stem cell transplantation (HSCT) and remains to be a major cause of mortality. Activation of toll-like receptor 4 (TLR-4) by lipopolysaccharide induces the NF-ΚB signaling pathway to release critical proinflammatory cytokines and increases the recipient response to GVHD. In order to clarify the role of TLR-4 in the occurrence of acute GVHD after HSCT, we collected 208 samples from HSCT recipients and their human lecucyte antigen identical donors to test the hypothesis that TLR-4polymorphism in the recipients or donors influence the risk of acute GVHD in allogeneic HSCT recipients. Methods: TLR-4 Asp299Gly and Thr399Ile polymorphisms of each sample were examined by using DNA sequencing and polymerase chain reaction-restriction fragment length polymorphism methods. Results: No homozygous or heterozygous variant alleles of the Asp299Gly or Thr339Ile polymorphism were detected in any samples in our study. Our results demonstrate that TLR-4 Asp299Gly and Thr399Ile polymorphisms might be very rare in the Chinese population (Eastern China and Taiwan region). Conclusion: The results of this study cannot confirm the role of TLR-4 mutations in the pathogenesis of GVHD in humans, yet we reach a definite conclusion by a TLR-4 knockout murine GVHD model in our ongoing project.
Keywords: chinese population